Mechanical behavior of hydrate-bearing pressure-core sediments visualized under triaxial compression. (September 2015) - Yoneda, Jun; Masui, Akira; Konno, Yoshihiro; Jin, Yusuke; Egawa, Kosuke; Kida, Masato; Ito, Takuma; Nagao, Jiro; Tenma, Norio
Abstract: Geomechanical and geotechnical properties are essential for evaluating the stability of deep seabed and subsea production systems for gas hydrate extraction from marine sediments. In this study, natural gas hydrate-bearing sediment was subjected to triaxial compression tests (shearing) using a newly developed triaxial testing system (TACTT) to investigate the geomechanical behavior of sediments recovered from below the seafloor in the eastern Nankai Trough, where the first Japanese offshore production test was conducted in 2013. The sediments were recovered using a hybrid pressure coring system, with pressure cores cut using onboard pressure core analysis tools. The pressure cores were subsequently transferred to our shore-based laboratory and subsampled using pressure core non-destructive analysis tools (PNATS) for the TACTT system. Pressure and temperature conditions were maintained within the hydrate stability boundary during coring and laboratory testing. An image processing technique was used to capture deformation of the sediment sample within the transparent acrylic test cell, and digital photographs were obtained for each 0.1% strain level experienced by the sample during the triaxial compression test. Analysis of the digitized images showed that sediments with 63% hydrate saturation exhibited brittle failure, whereas hydrate-free sediments exhibited ductile failure. The increase in shear strength with increasing hydrate saturation in natural gas hydrates is in agreement with previous data from sediments containing synthetic gas hydrates. Highlights: Triaxial test of methane hydrate-bearing pressure core sediments was conducted. Pressure core was visualized under in situ pressure from observation window. Strength and stiffness of intact methane hydrate-bearing sediments were measured. Brittle failure mode of hydrate-bearing sediments was observed. Strain localization was quantified by image processing technique.